Dislocation-toughened ceramics. Issue 5 (16th March 2021) - Porz, Lukas; Klomp, Arne J.; Fang, Xufei; Li, Ning; Yildirim, Can; Detlefs, Carsten; Bruder, Enrico; Höfling, Marion; Rheinheimer, Wolfgang; Patterson, Eric A.; Gao, Peng; Durst, Karsten; et al.
Abstract : Dislocations are mobile at low temperatures in surprisingly many ceramics but sintering minimizes their densities. Enabling local plasticity by engineering a high dislocation density is a way to combat short cracks and toughen ceramics. Abstract : Functional and structural ceramics have become irreplaceable in countless high-tech applications. However, their inherent brittleness tremendously limits the application range and, despite extensive research efforts, particularly short cracks are hard to combat. While local plasticity carried by mobile dislocations allows desirable toughness in metals, high bond strength is widely believed to hinder dislocation-based toughening of ceramics. Here, we demonstrate the possibility to induce and engineer a dislocation microstructure in ceramics that improves the crack tip toughness even though such toughening does not occur naturally after conventional processing. With modern microscopy and simulation techniques, we reveal key ingredients for successful engineering of dislocation-based toughness at ambient temperature. For many ceramics a dislocation-based plastic zone is not impossible due to some intrinsic property ( e.g. bond strength) but limited by an engineerable quantity, i.e. the dislocation density. The impact of dislocation density is demonstrated in a surface near region and suggested to be transferrable to bulk ceramics. Unexpected potential in improving mechanical performance of ceramics could be realized with novel synthesis strategies.